Social Studies Learning as a Means of Transforming Students’ Social Sensitivity: A Quantitative Study - Trian, Rima; Suliani, Sri (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aimed to examine the influence of Social Studies learning on students’ social sensitivity, particularly in developing empathy, social awareness, self-awareness, and mutual respect among junior high school students through effective and interactive classroom learning processes within the educational environment. Methodology: This study employed a quantitative associative research design involving 30 junior high school students selected through total sampling techniques. Data were collected using observation sheets, questionnaires, and documentation methods. Research instruments applied a Likert scale measurement model. Data analysis included normality tests, heteroscedasticity tests, simple linear regression, coefficient determination, and hypothesis testing using IBM SPSS Statistics 25 software. Main Findings: The findings indicated that Social Studies learning had a positive and significant influence on students’ social sensitivity. Students demonstrated good levels of empathy, social awareness, self-awareness, and mutual respect during the learning process. Regression analysis showed a significance value of 0.000 and a coefficient determination value of 87.2%, indicating that Social Studies learning substantially contributed to improving students’ social sensitivity within the school environment. Novelty/Originality of this study: This study highlights social sensitivity as the primary outcome of Social Studies learning using a quantitative associative approach. Unlike previous studies emphasizing cognitive achievement, this research focuses on the transformation of students’ social character through Social Studies learning. The study also provides empirical evidence regarding the contribution of Social Studies learning to strengthening students’ interpersonal awareness and social behavior.